2018
DOI: 10.1111/jfs.12549
|View full text |Cite
|
Sign up to set email alerts
|

Microbial quality of edible grasshoppers Ruspolia differens (Orthoptera: Tettigoniidae): From wild harvesting to fork in the Kagera Region, Tanzania

Abstract: In Tanzania, edible Ruspolia differens are still harvested from the natural environments. In this perspective, little is known about the microbiological quality of wild harvested R. differens. This study was conducted to assess the microbiological quality of wild harvested R. differens and evaluate the efficacy of conventional processing methods in reducing microbial load. Two districts (Bukoba rural and Muleba) within the Kagera region were purposively selected for the study. Sampling was done from the same b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…The boiling and toasting procedures applied in the present study potentially eliminated E. coli and other enteric pathogens. Other authors, [47,48], made similar observations on boiled I. belina larvae and toasted R. differens, respectively. Staphylococcus aureus was present on all the raw products ( Table 5).…”
Section: Effects Of Boiling and Toastingsupporting
confidence: 60%
See 1 more Smart Citation
“…The boiling and toasting procedures applied in the present study potentially eliminated E. coli and other enteric pathogens. Other authors, [47,48], made similar observations on boiled I. belina larvae and toasted R. differens, respectively. Staphylococcus aureus was present on all the raw products ( Table 5).…”
Section: Effects Of Boiling and Toastingsupporting
confidence: 60%
“…Similar findings were reported for boiled (5-10 min) G. sigillatus [16], boiled (ca. 93 • C; 30 min) I. belina [47] and toasted (10 min) R. differens [48]. The interaction effect of insect species and processing method was significant for the destruction of TVC (F = 1207; df = 35; p < 0.001) and YMC (F = 11739.6; df = 35; p < 0.001).…”
Section: Effects Of Boiling and Toastingmentioning
confidence: 96%
“…Therefore, for the interest of food safety, the presence of Listeria in insects, especially potentially edible insects, has been an ongoing investigation. In numerous other surveys of insects, including bush crickets (Ruspolia diffferens), lesser mealworms (Alphitobius diaperinus), tropical house crickets (Gryllodes sigillatus), field crickets (Gryllus bimaculatus), superworms (Zophobas atratus), and cockroaches, no Listeria has been found [60][61][62][63][64]. This absence of Listeria in insects, despite the prevalence of Listeria in natural environments [65], might result from Listeria acting as an insect pathogen.…”
Section: Discussionmentioning
confidence: 93%
“…The rich nutritional value of edible insects coupled with high moisture content provide a conducive environment for microbial contamination, survival and growth (Klunder et al, 2012;Van Huis, et al, 2013). Microorganisms can also be introduced along the food handling chain, causing food spoilage or disease outbreaks (Ng'ang'a et al, 2019;Ssepuuya et al, 2019). Intrinsic factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…the migratory locust, Locusta migratoria L (Orthoptera: Acrididae) and mealworm, Tenebrio molitor L (Coleoptera: Tenebrionidae) (Garofalo et al, 2017;Stoops et al, 2016); crickets, Acheta domesticus L and Gryllodes sigillatus (Walker) (Orthoptera: Gryllidae) Vandeweyer et al, 2017); and the long-horned grasshopper, Ruspolia differens (Serville) (Orthoptera: Tettigoniidae) (Ng'ang Ssepuuya et al, 2019). Counts of total aerobic microbes, yeasts and moulds higher than the maximum standard limits set out in standards for edible insects (KEBS, 2020;Stoops et al, 2016;UNBS, 2020) have been reported in wild harvested raw R. differens (Ng'ang'a et al, 2019;Ssepuuya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%